2019
DOI: 10.1186/s12879-019-4624-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of hepatitis B surface antigen gene in the preserved umbilical cords in immunoprophylaxis failure against mother-to-child HBV transmission

Abstract: BackgroundVaccine escape mutants (VEMs) are one of the causes of breakthrough infections in the mother-to-child transmission of hepatitis B virus (HBV). We hypothesized that VEMs existing as minor populations in the maternal blood are associated with breakthrough infections in children. We sought to determine whether VEMs exist as minor populations in the preserved umbilical cords of children with breakthrough infections.Case presentationTwo families (Family 1: three children, Family 2: two children) were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…On the basis of the growth rate, nail clippings could retain HBV DNA at least several months after the disappearance of serum HBV DNA. Previously, we reported a mother-to-child transmission case in which a past time frame of nails contributed to the detection of vaccine scape mutant [ 37 ]. In the report, a 2-year-old boy was chronically infected through breakthrough infection and G145R vaccine escape mutant was detected in his serum.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the growth rate, nail clippings could retain HBV DNA at least several months after the disappearance of serum HBV DNA. Previously, we reported a mother-to-child transmission case in which a past time frame of nails contributed to the detection of vaccine scape mutant [ 37 ]. In the report, a 2-year-old boy was chronically infected through breakthrough infection and G145R vaccine escape mutant was detected in his serum.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the growth rate, nail clippings could retain HBV DNA at least several months after the disappearance of serum HBV DNA. Previously, we reported a mother-tochild transmission case in which a past time frame of nails contributed to the detection of vaccine scape mutant [39]. In the report, a 2-year-old boy was chronically infected through breakthrough infection and G145R vaccine escape mutant was detected in his serum.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the integration of HBV DNA into host genomic DNA is observed in peripheral blood cells (6) , (7) . Recent studies have shown that HBV DNA can be detected in the nails and hair of patients with acute and chronic HBV infection (8) , (9) , (10) . In addition to HBV, cytomegalovirus (CMV) DNA was detected in the nails of a child with congenital CMV infection (11) .…”
Section: Introductionmentioning
confidence: 99%